High-level production of the non-cariogenic sucrose isomer palatinose in transgenic tobacco plants strongly impairs development - Sonnewald, Uwe; et al. (Planta, 2002)
Palatinose (isomaltulose, 6-O-alpha-D-glucopyranosyl-D-fructose) is a structural isomer of sucrose which is produced from sucrose by some bacterial strains as a reserve material during periods of low carbon availability. The ability to synthesise palatinose is not only advantageous for the bacteria but is also of industrial interest since palatinose is used as a sucrose substitute in food production. To explore the possibility of palatinose production in plants a recently isolated sucrose isomerase gene (palI; EC 5.4.99.11) from Erwinia rhapontici [F. Bornke et al. (2001) J Bacteriol 183: 2425-2430] was cloned into a plant expression vector between the constitutive 35S CaMV promoter and the octopine synthase polyadenylation signal. To allow secretion of the protein into the apoplast the signal peptide of the potato proteinase inhibitor 11 was N-terminally fused to the palI coding region. Expression of the protein was verified by northern and western blot analyses. Efficient secretion of the protein was demonstrated by palI detection in intercellular fluids. Transgenic plants expressing palI accumulated high levels of palatinose. As a consequence, transgenic plants showed severe phenotypic alterations. Young leaves were curled and developed bleached areas during maturation. Flowers were misshapen and sterile. Based on nonaqueous fractionation experiments palatinose was found in several subcellular compartments, indicating limited membrane transport of the sugar. In contrast to results obtained with short-term feeding experiments, no evidence for palatinose-mediated regulation of photosynthetic or defence genes could be obtained in the transgenic pall-expressing tobacco plants. Based on our results we conclude that plants can efficiently be used as bioreactors for the production of palatinose. Furthermore, tissue-specific expression of pall should allow carbon allocation to specific tissues and/or cell-types to be modulated.
Keywords: Nicotiana (palatinose); palatinose; sucrose isomerase; transgenic tobacco